The effects of rifampicin and fluoroquinolones on tubercle bacilli within human macrophages - (:unkn) unknown (ELSEVIER SCIENCE BV, 2004)
The objective of this study was to determine the activities of rifampicin, ciprofloxacin and sparfloxacin against M. tuberculosis H37Rv in human macrophages. The minimal inhibitory concentrations (MIC) were determined by agar macrodilution and broth microdilution methods and were 0.5, 1 and 0.125 mg/l, respectively. Concentrations of rifampicin at 0.5 and 2.5 mug (P < 0.001), ciprofloxacin at 4 and 8 mug (P < 0.001) and sparfloxacin at 0.125 mug (P < 0.05), 0.625 mug (P < 0.001) and 1.25 mug (P < 0.001) were found to be effective against intracellular bacteria. Ciprofloxacin and especially sparfloxacin were effective in macrophages and may be useful in the treatment of tuberculosis particularly infections caused by multiply drug resistant strains. (C) 2003 Published by Elsevier B.V. and the International Society of Chemotherapy.
Keywords: M. tuberculosis; human macrophage; rifampicin; fluoroquinolones; CULTURED HUMAN MACROPHAGES; MYCOBACTERIUM-AVIUM COMPLEX; COMPARATIVE ANTIMYCOBACTERIAL ACTIVITIES; IN-VITRO ACTIVITY; FLUORINATED QUINOLONES; PULMONARY TUBERCULOSIS; SPARFLOXACIN AT-4140; ANTIMICROBIAL AGENTS; CLARITHROMYCIN; CIPROFLOXACIN